2021
DOI: 10.1186/s12871-021-01335-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative X-ray C2C6AR is applicable for prediction of difficult laryngoscopy in patients with cervical spondylosis

Abstract: Background Airway management is one of the most important techniques in anesthesia practice and inappropriate airway management is related with airway injury, brain hypoxia, and even death. The patients with cervical spondylosis are often confronted with difficult laryngoscopy who are more prone to appear difficult airway, so it is important to figure out valuable predictors of difficult laryngoscopy in these patients. Methods We randomly enrolled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The incidence of airway difficulties in patients with occipito-atlanto complex lesions was higher than that in patients with disease below the complex [ 48 ]. Label-3 achieved the best performance, and might represent the best indicator of challenging laryngoscopy reflecting cervicale movability, consistent with previous result [ 5 ]. The results demonstrated that label-3 was slightly better than label-2, and both were slightly better than label-1.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The incidence of airway difficulties in patients with occipito-atlanto complex lesions was higher than that in patients with disease below the complex [ 48 ]. Label-3 achieved the best performance, and might represent the best indicator of challenging laryngoscopy reflecting cervicale movability, consistent with previous result [ 5 ]. The results demonstrated that label-3 was slightly better than label-2, and both were slightly better than label-1.…”
Section: Discussionsupporting
confidence: 90%
“… Label-2: Atlanto-occipital distance [ 6 ]. Label-3: The corner between the lower margin of the second vertebrae cervicale and the lower margin of the sixth vertebrae cervicale in neutral position [ 5 ].
Figure 5 Labelled laryngoscope X-ray.
…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations